Contribution of Terrestrial Runoff to Coral Disease Prevalence on North Bali’s Massive Porites - I Gusti Bagus Siladharma; Widiastuti Karim (Marine Science Department Diponegoro University, 2017)
The widespread of coral disease may threatened Bali`s marine tourism which is the main asset for the nation prosperity. However, the disease prevalence is still unknown, in particular inshore coral reefs near to tourist spot areas. Therefore, the research aims to investigate the contribution of terrestrial runoff to coral disease prevalence and to examine the relationships between disease prevalence and environmental parameters (nitrate, phosphate, organic carbon and total suspended solids (TSS)) within the population of massive Porites on shallow north Bali reefs. Syndrome, diseases and healthy colonies of massive Porites coral were counted and noted within a 2 x 10 m belt transect at 3 sampling sites. The dominant disease observed was ulcerative white spots (UWS), while the syndromes were pigmentation response and aggressive overgrowth by macroalgae. The highest mean UWS prevalence was at site 3 which was the closest site to runoff (prevalence = 91%).This disease only affected one colony at site 1 and 2, respectively. Disease prevalence had strong relationship with TSS and nitrate, yet it showed weak relationship with phosphate and organic carbon. These results suggest that terrestrial runoff could contribute to the disease prevalence by increasing the TSS, nutrients and organic carbon loading to the inshore ecosystems. High level of organic carbon could severe the disease, particularly when combined with elevated TSS and nutrient, by reducing the coral`s immunity system. Keywords: coral disease, prevalence, terrestrial runoff, Porites, ulcerative white spot, environmental parameter, North Bali.